Polymeric nanoformulation prototype based on a natural extract for the potential treatment of type 2 diabetes mellitus (2023)
ABSTRACT: Triterpene-enriched fractions (TFs) from Eucalyptus tereticornis demonstrated efficiency when administered intraperitoneally in diet-induced obesity (DIO) mouse model to treat obesity-related type 2 diabetes mellitus (T2DM); however, its oral administration has not yet led to satisfactory results. In this context, we developed a polymeric nanoformulation to transport TFs orally in DIO mice and control obesity and T2DM effects. We encapsulated TFs in a polylactic-co-glycolic acid-based nanocarrier, physicochemically characterized the nanocarriers, and evaluated TFs in-vitro release kinetics, in-vivo metabolic biomarkers, and released triterpenes in a simulated in-vitro human gastrointestinal model. The nanoformulation showed a TFs release of 80% in the first 6h in-vitro, and the in-vivo assay demonstrated a decrease in mice weight, glycaemia, glucose, and insulin intolerance. Finally, triterpenes released up to 75% in the simulated in-vitro human intestine. These results open the way for developing new strategies of therapeutic agents with natural products to control obesity and T2DM.